O litígio na fronteira entre Rondônia e Acre: as disputas políticas e o impacto na vida da população (1986-1996) - Gama, Ediléia Ferreira (2024)
This research analyzes the litigation process occurred in the border between Acre and Rondônia, in the period from 1986 to 1996. It has happened when, from the final of the 1970 decade and the beginning of the eighties, Acre started to broaden the borders towards Rondônia’s lands, in the aim of attend the population’s demands, as the educations sphere, health, security and bank branch. The progress over Rondônia’s lands became consolidated enough to make people from Acre feel free to register their residents as voters of the TER/AC. In 1986, the governor, Jerônimo Santana, sent troops to the region and started the process of reclaiming the domains of Rondônia. The population, initially territorialized with Acre didn’t support Rondônia’s claim. As the time passed, both states diminished in the services offer ands the population claimed the end of the litigation. Which happened in 1996, June, leaving economic and cultural scars. People have been fighting for political emancipation for a decade. In addition to these supports, documentation research was done in the Federal Constitution (1988) and other complementary laws. To emphasize the situation related to this litigation, research was also a field survey was done through a semi-open questionnaire on Google Forms to analyze the sense of belonging among the residents today. The answers indicate a material sense of belonging due to the physical practicality with Acre, but cultural belonging is related to the sense of community and experiences with the local territory.